Current Challenges for Conscientious Objection by Physicians in Spain - Soriano, Vicente; Montero, Borja (Linacre Quarterly, 2024)
The College of Physicians of Madrid organized an open debate on conscientious objection (CO) in the medical profession on September 14, 2022. We summarize here the main arguments discussed. CO is defined as the right to raise exceptions to the performance of legal duties when they involve a contravention of personal convictions, whether religious, moral, or philosophical. It is not insubordination. Some authors contend that any decision by elected authorities should be uniformly followed by all citizens, physicians not being an exception. However, suppressing the ethical dimension of medical care may have an unacceptable cost with harm to physicians, their patients, and ultimately society. Health professionals are not blind instruments or mere "executors." The practice of medicine must follow the aim of the profession, namely the pursuit of the patient's good. Medical care must conform to medical ethics, which was first defined twenty-five centuries ago in the Hippocratic oath, and summarized with the triad of precepts "cure, relief, accompaniment." Since then and particularly in light of the Nuremberg trials, most medical declarations have highlighted the duty of defending human life and the importance of CO. In modern societies, there may be medical services that are not health care, even if they are legal. Then, which comes first law or ethics? Ultimately, CO is the tool that protects the freedom of the physician to refuse to perform actions that go against the values of medical ethics. With respect to the recent Spanish laws on abortion, euthanasia, and sex re-assignment of minors, if administrators want to know who is available for a health service that raises issues of conformity to medical ethics, requesting a list of volunteers is preferable to producing an objector list. Asking for registration of conscientious objectors goes against the right to privacy and is coercive, intrusive, and abusive.
Keywords: abortion; conscientious objection; euthanasia; fundamental rights; medical duty; emerging